Eksperimen Model Pembelajaran Make a Match dan Teams Game Tournament (TGT) dalam Pembelajaran Matematika Ditinjau dari Kedisiplinan Belajar Siswa Kelas VIII SMP Negeri 1 Surakarta - Griyati, Nopriana Mangun; , Rita Pramujiyanti Khotimah, S.Si., M.Sc (2017)
The aim of this research was to know: (1) The influence of the learning model Make A Match and Teams Games Tournament (TGT) to the learning outcomes of students. (2) The nfluence of student's discipline to student learning outcomes. (3) The interaction effect between learning model and student's discipline towards student's mathematics learning outcomes. The research was a quasi-experimental research. The research population was 8th grade students of SMP Negeri 1 Surakarta in 2016/2017. Samples of this research was VIII A and VIII C class. The sampling technique was cluster random sampling. The data collection was done with the test, questionnaire and documentation. The data was analyzed using two-way analysis of variance with different cells. This research concluded that: (1) There is an effect of learning model Make a Match and Teams Games Tournament (TGT) to the learning outcomes of students with Fa= 4,56. (2) There is student's discipline effect on learning outcomes of students with Fb= 5,108. (3) There is interaction effect between the model of learning and student's discipline towards mathematics learning outcomes of students with Fab= 3,319.